Leading Hybrid Public Organizations: Institutional Pathways and IndirectLeadership Effects in State University Teaching Hospitals (RSPTN) - Katarina Sri Nenggih Wahyuni; Agus Heruanto Hadna; Muhadjir Darwin; Yodi Mahendradhata (Pelopor Publikasi Akademika, 2026)
This study aims to analyze the role of leadership in influencing organizational performance in State University Teaching Hospitals (RSPTN) as hybrid public organizations facing institutional complexity. The research employs a mixed-methods approach with a sequential explanatory design, combining quantitative analysis using PLS-SEM and qualitative analysis through in-depth interviews. The findings reveal that leadership does not have a direct effect on organizational performance but rather operates through indirect pathways mediated by learning organizations and institutional characteristics. These results indicate that in hybrid organizations, leadership effectiveness is highly dependent on institutional context and the organization’s capacity for learning and adaptation. Qualitative findings further demonstrate that leadership plays a crucial role in navigating institutional complexity, strengthening organizational learning, and distributing authority in a collective manner. This study contributes to the leadership literature by highlighting that the relationship between leadership and performance is indirect and context-dependent. Practically, the findings suggest that strengthening leadership in RSPTN should be accompanied by the development of learning organizations and the alignment of institutional governance to enhance sustainable organizational performance.